Numerical and experimental evaluation and optimization of ceramic foam as solar absorber – Single-layer vs multi-layer configurations. (15th January 2018) - Zaversky, Fritz; Aldaz, Leticia; Sánchez, Marcelino; Ávila-Marín, Antonio L.; Roldán, M. Isabel; Fernández-Reche, Jesús; Füssel, Alexander; Beckert, Wieland; Adler, Jörg
Highlights: The thermal efficiency of ceramic foam absorbers depends strongly on their porosity. The highest possible porosity should be chosen for future solar receiver designs. A flat efficiency maximum can be observed for cell densities between 30 and 50 PPI. An optimized single-layer configuration is the absorber of choice. Multi-layer configurations do not have any advantage regarding thermal performance. Abstract: This work targets the numerical and experimental evaluation of ceramic foam as solar absorber material for solar thermal power generation. Two different 1-D model types with local thermal non-equilibrium (LTNE) have been developed independently at CENER and Fraunhofer-IKTS. The modeling of radiation propagation inside the foam is considered via two approaches. One approach is based on a discrete-ordinate solution of the radiation transport equation; the other imposes the solar flux defining an exponential attenuation, as derived from Bouguer's law, and considering thermal radiation transport according to Rosseland's diffusion approximation. Both models have been successfully checked for consistency against experimental data obtained at a 4 kW solar simulator. Then, the models have been run applying automatic scripts, performing a large number of parameter variations, optimizing for the absorber thermal efficiency. It is important to note that single, double and triple layer absorber configurations have been studied, since previous works found that a decreasing porosity in direction of flow can enhance absorber performance. The parametric optimization studies have shown that the porosity of the foam is strongly related to the obtained thermal efficiency. The higher the porosity of the foam, the higher is also the absorber thermal efficiency. A broad plateau-like efficiency maximum can be observed for cell densities between 30 and 50 PPI (pores per inch). When applying a multi-layer configuration, no significant correlation can be observed between efficiency and the properties of the second or third layer. Only the parameters of the first layer seem to determine the thermal performance. This leads to the conclusion that an optimized single-layer configuration is the absorber of choice. If necessary, a second layer could be applied to satisfy mechanical stability aspects.